2021
DOI: 10.1177/2192568221991510
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Between the Perioperative Outcomes of Female Adolescent Idiopathic Scoliosis (AIS) Versus Adult Idiopathic Scoliosis (AdIS) Following Posterior Spinal Fusion: A Propensity Score Matching Analysis Involving 425 Patients

Abstract: Study Design: Retrospective propensity score matching (PSM) study. Objective: To investigate the perioperative outcomes comparing adolescent idiopathic scoliosis (AIS) and adult idiopathic scoliosis (AdIS) patients following posterior spinal fusion (PSF). Methods: 425 female AIS and AdIS patients who were operated (between January 2015 to March 2020) using a dual attending surgeon strategy were stratified into G1 (AIS aged 10-16 years old) and G2 (AdIS > 20 years old). PSM analysis with one-to-one, nearest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…The use of PSM (propensity score matching) analysis in our clinical study allowed for a good correction of selectivity bias, which was confirmed in many previous studies [18][19][20][21]. SPSS used version 22.0 (SPSS, Inc., Chicago, IL, USA), and P value < 0.05 was considered statistically significant.…”
Section: Discussionmentioning
confidence: 59%
“…The use of PSM (propensity score matching) analysis in our clinical study allowed for a good correction of selectivity bias, which was confirmed in many previous studies [18][19][20][21]. SPSS used version 22.0 (SPSS, Inc., Chicago, IL, USA), and P value < 0.05 was considered statistically significant.…”
Section: Discussionmentioning
confidence: 59%
“…The triplanar correction rate of the technique proved to be really efficient with excellent correction rates in terms of coronal and sagittal correction (70.1% correction of the main curve, 57.9% increase in TK and 32% increase in LL). Indeed, the obtained 70.1% of coronal correction is superior to the higher percentage of correction observed in the literature [2,5,13,20]. Only Zhu et al [21] reported similar correction rates (up to 71%) but in younger patients (22.2 years old) with flexible curves (curve flexibility of 48%).…”
Section: Discussionmentioning
confidence: 71%
“…Hi-PoAD technique, although technically demanding, resulted in average operative time and blood loss equal or inferior to the principal case series dealing with AdIS [2,5,13,20,21]. It also proved to be efficient in respect surgical planning, with no need to extent the fusion area due to screw pull-out at the most cephalad and caudal levels, meaning that the procedure is really effective in dissipating corrective forces avoiding intra-operative mechanical complications.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations